On application of linear algebra in classification cubic s-regular graphs of order 28p - Imani, A.; Mehdipoor, N.; Talebi, A.A. (Algebra and Discrete Mathematics, 2018)
A graph is s-regular if its automorphism group acts regularly on the set of s-arcs. In this paper, by applying concept linear algebra, we classify the connected cubic s-regular graphs of order 28p for each s ≥ 1, and prime p.